2017
DOI: 10.4028/www.scientific.net/msf.897.614
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neutron Irradiation on Epitaxial 4H-SiC PiN UV<sup></sup>-Photodiodes

Abstract: 4H-SiC UV-photodetectors based on full-epitaxial p +p-n+ multilayer structures werefabricated. The diodes were irradiated with fast neutrons up to the fluence of 1·1014 cm-2 . Current-voltage characteristics, life time of non-equilibrium charge carriers as well as photosensitivityspectra of the diodes before and after irradiation were investigated. The studies showed that PiNUV-photodiodes with base doping below 1·1015 cm-3 retain their performance up to the fluence of5·1012 neutrons per cm2 . The further incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Afanasyev, et al, [37] examined the photosensitivity of SiC UV photodiodes and observed no change in performance after a fast-neutron fluence of 5 x 10 12 cm -2 but observed reduction of the photosensitivity of their devices at higher fluences up to 1 x 10 14 cm -2 .…”
Section: Detectorsmentioning
confidence: 99%
“…Afanasyev, et al, [37] examined the photosensitivity of SiC UV photodiodes and observed no change in performance after a fast-neutron fluence of 5 x 10 12 cm -2 but observed reduction of the photosensitivity of their devices at higher fluences up to 1 x 10 14 cm -2 .…”
Section: Detectorsmentioning
confidence: 99%